Análise da estrutura tridimensional, especificidade e atividade anticâncer da lectina Canavalia villosa (Benth) - Lóssio, Cláudia Figueiredo (2021)
Cells use surface glycans to encode information that modulates processes ranging from cell recognition and tissue development to apoptosis. The decoding of these messages stored in a glycocode is performed by carbohydrate-binding molecules, and among these, lectins stand out as they are well-characterized proteins that bind to glycans in a highly specific and reversible way. Thus, lectins may be able to recognize specific cell types according to the glycosylation profile expressed in the membranes of these cells. It is known that several pathologies, including cancer and diabetes, present mutated glycans on the surfaces of affected tissues. This fact raises interest in the area of glycobiology and lectinology as these fields try to unravel the relationship among the message conveyed by altered carbohydrates and the development and progression of diseases. In view of this, the bioprospection and characterization of new lectins that may have biotechnological potential is interesting in view of the proven applications that known lectins have presented so far. This work aimed to analyze the anticancer activity of the lectin from Canavalia villosa (Cvill), drawing a parallel among the lectin toxicity and its carbohydrate affinity profile. The three-dimensional structure of this lectin was also solved and used to analyze interactions with cancer glycans in silico. For this, Cvill, which was isolated and partially characterized previously, had its amino acid sequence determined by mass spectrometry and gene sequencing. The three-dimensional structure was solved by macromolecule crystallography and X-ray diffraction. The fine carbohydrate specificity of Cvill was studied by Glycan Array and Molecular Docking, and its anticancer activity was evaluated in HeLa cells, in which ROS production and caspase activation were assessed. The level of apoptosis and autophagy transcripts expression was analyzed by qPCR. The results showed that Cvill has a cytotoxic effect on HeLa cells, with participation of CRD and generation of intracellular ROS at the highest dose tested. It was also observed that cell death was triggered by mechanisms involving both autophagic and apoptotic pathways, with increased expression of LC3 and activation of caspases 8. Cvill presents a three-dimensional structure typical of legume lectins, with a β-sandwich domain and conserved carbohydrate and metal binding sites.